Dietary supplementation of L-tryptophan: Effect on growth and survival of Pabda, Ompok bimaculatus (Bloch) fry. Issue 4 (2nd October 2019) - Biswas, Pradyut; Rawat, Priya; Patel, Arun Bhai; Jena, Alok Kumar
ABSTRACT: A 30-day experiment was conducted to assess the effect of tryptophan-supplemented diets on growth and survival of Pabda, Ompok bimaculatus fry. Fifty pabda fry (0.114 ± 0.02 g; 2.45 ± 0.13 cm) were stocked into each aerated aquarium following a completely randomized design consisting of four treatments with triplicate each. Four iso-proteinious purified diets were prepared with different levels of tryptophan—0%, 1%, 2%, and 3%—of the dry diet and were designated as Control, TRP1, TRP2, and TRP3 respectively. Fishes were fed with the experimental diet ad libitum four times a day. The results showed that fish fed with tryptophan-supplemented diets exhibited significantly (P < 0.05) lower cannibalism and higher survival than the control diet. Further, the tryptophan-supplemented groups showed a significantly lower coefficient of variation (%) and size heterogeneity (P < 0.05). However, the growth as measured by body weight gain, length increment, and specific growth rate of fry in tryptophan-supplemented groups was significantly lower than the control group (P < 0.05). Moreover, maximum survival (52.67 ± 1.76%) and minimum cannibalism (21.33 ± 5.70%) coupled with higher growth and performance index (0.38 ± 0.01) were recorded in the 2% tryptophan-supplemented group compared to other tryptophan-fed groups. Overall interpretation from the present study concludes that the dietary supplementation of 2% tryptophan is recommended for better survival of pabda fish, although growth was compromised.